Evaluating protected area effectiveness using bird lists in the Australian Wet Tropics. Issue 4 (3rd November 2014) - Barnes, Megan; Szabo, Judit K.; Morris, William K.; Possingham, Hugh; Rouget, Mathieu
Abstract Aim Protected areas underpin many global conservation efforts. However, it is often unclear whether they are effective in maintaining their biodiversity values, both absolutely, and also relative to other conservation actions or land uses. Longitudinal population data are critical for determining protected area performance robustly, but such data are rare. As such, there is often insufficient information with which to make adequate, informed decisions for policy and management. Conversely, informally collected data, such as species lists, are common, especially for birds, and they are often the only source of historical data. The aim of this study was to use list data to evaluate the contribution of protected areas to the conservation of endemic birds. Location Wet Tropics bioregion of Queensland, Australia. Methods We used a list‐length analysis (LLA), a recently developed approach. We estimate trends in species populations with a Bayesian logistic regression to infer bird presence from non‐standardized volunteer‐collected bird surveys from the New Atlas of Australian Birds that were conducted both inside and outside protected areas. Results Overall, the prevalence of the majority of wet tropics endemics (18 of 21) has been stable since 1998. Sixteen species were more likely to be found within protected areas, two were more likely to be recorded outside, and three showed little difference. However, there was no difference in trends in prevalence between protected and unprotected areas for all but one endemic species. Main conclusions Where formal data collection is too expensive or time consuming, it may still be possible to inform decision‐making when citizen‐collected species list data are available. In the Wet Tropics, our results suggest that for the majority of the species, protected areas may contain better habitat than unprotected areas, but that birds inside protected areas are not significantly better off through time than birds outside protected areas, as long as forest outside protected areas remains intact.